2020
DOI: 10.2147/ott.s266449
|View full text |Cite
|
Sign up to set email alerts
|

<p>Yes-Associated Protein Contributes to Cell Proliferation and Migration of Gastric Cancer via Activation of Gli1</p>

Abstract: Objective In the present study, we aimed to explore the potential oncogenic property and the internal mechanism of yes-associated protein (YAP) in gastric cancer (GC). Materials and Methods YAP protein levels were evaluated in human GC tissues and paired normal tissues using immunohistochemistry (IHC). The role of YAP in regulating GC cell proliferation and migration was verified by genetic manipulation in vitro. Western blot analysis was used to determine the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Gli1 was silenced in HCT116 cells with or without LATS1 depletion to see if it was involved in LATS1 regulation of CRC cell proliferation and migration and it was observed that LATS1 knockdown promoted the migration and proliferation of HCT116 cells, but the enhanced proliferation and migration ability was greatly impaired when Gli1 was depleted, indicating the dependence of anti-carcinogenic roles of LATS1 on Gli1. Given the facts that LATS1 is a critical regulator of YAP1 [5] and YAP1 can upregulate Gli1 expression in esophageal squamous cell carcinoma [30] and gastric cancer [31], we speculated that YAP1 might be implicated in LATS1-mediated Gli1 suppression. Here, we confirmed that LATS1 depletion promoted YAP1 expression while LATS1 elevation inhibited YAP1 expression in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gli1 was silenced in HCT116 cells with or without LATS1 depletion to see if it was involved in LATS1 regulation of CRC cell proliferation and migration and it was observed that LATS1 knockdown promoted the migration and proliferation of HCT116 cells, but the enhanced proliferation and migration ability was greatly impaired when Gli1 was depleted, indicating the dependence of anti-carcinogenic roles of LATS1 on Gli1. Given the facts that LATS1 is a critical regulator of YAP1 [5] and YAP1 can upregulate Gli1 expression in esophageal squamous cell carcinoma [30] and gastric cancer [31], we speculated that YAP1 might be implicated in LATS1-mediated Gli1 suppression. Here, we confirmed that LATS1 depletion promoted YAP1 expression while LATS1 elevation inhibited YAP1 expression in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Given the facts that LATS1 is a critical regulator of YAP1 5 and YAP1 can upregulate Gli1 expression in esophageal squamous cell carcinoma 30 and gastric cancer 31 , we speculated that YAP1 might be implicated in LATS1-mediated Gli1 suppression. Here, we confirmed that LATS1 depletion promoted YAP1 expression while LATS1 elevation inhibited YAP1 expression in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, FLangan et al found that Wnt receptor Fzd7 played an essential role in gastric tumorigenesis [48]. YAP was also reported to enhance GC cell proliferation and migration by regulating Gli1 expression via the non-classical Hedgehog pathway [49]. We observed that β-catenin binds to the promotor region of YAP, upregulating YAP expression and correlates with poor prognosis.…”
Section: Discussionmentioning
confidence: 49%
“…To knockdown (KD) TYRO3 expression, TYRO3 shRNA oligonucleotides were designed, synthesized, and transfected into AGS and MKN74 cells with 50 nM of the Lipofectamine™ RNAiMAX Transfection Reagent (Invitrogen) according to the manufacturer's instructions. AGS and MKN74 cells stably expressing TYRO3‐specific shRNA (KD) and mock transfection (a negative control [NC]) were generated using the lentivirus shRNA technique 19 . The human TYRO3 shRNA target sequence was CAAAGAGATGTCCTTGTAATA 20 .…”
Section: Methodsmentioning
confidence: 99%
“…AGS and MKN74 cells stably expressing TYRO3-specific shRNA (KD) and mock transfection (a negative control [NC]) were generated using the lentivirus shRNA technique. 19 The human TYRO3 shRNA target sequence was CAAAGAGATGTCCTTGTAA TA. 20 After 48 h of transfection, the AGS and MKN74 cells were collected and shRNA transfection efficiencies were detected through western blot analysis and quantitative real-time PCR (qRT-PCR).…”
Section: Shrna Transfectionmentioning
confidence: 99%